2019
DOI: 10.1021/acs.jpclett.9b02599
|View full text |Cite
|
Sign up to set email alerts
|

Borophosphene: A New Anisotropic Dirac Cone Monolayer with a High Fermi Velocity and a Unique Self-Doping Feature

Abstract: Two-dimensional (2D) Dirac cone materials exhibit linear energy dispersion at the Fermi level, where the effective masses of carriers are very close to zero and the Fermi velocity is ultrahigh, only 2 ~ 3 orders of magnitude lower than the light velocity. Such the Dirac cone materials have great promise in high-performance electronic devices. Herein, we have employed the genetic algorithms methods combining with first-principles calculations to propose a new 2D anisotropic Dirac cone material, that is, orthorh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 59 publications
(110 reference statements)
4
51
0
Order By: Relevance
“…The calculated values of four constants C 11 , C 12 , C 22 , and C 44 are 311.1, 79.3, 306.6, and 34.5 N m À1 , which fulfill the requirements of mechanical stability for an orthorhombic 2D monolayer (C 11 > 0, C 22 > 0, C 44 > 0, and C 11 C 22 > C 2 12 ). [45] We can also obtain the in-plane Young's modulus and Poisson's ratio along an arbitrary direction θ (θ is the angle relative to the primitive vectorã in Figure 1a) by the following formula. [66] YðθÞ ¼…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated values of four constants C 11 , C 12 , C 22 , and C 44 are 311.1, 79.3, 306.6, and 34.5 N m À1 , which fulfill the requirements of mechanical stability for an orthorhombic 2D monolayer (C 11 > 0, C 22 > 0, C 44 > 0, and C 11 C 22 > C 2 12 ). [45] We can also obtain the in-plane Young's modulus and Poisson's ratio along an arbitrary direction θ (θ is the angle relative to the primitive vectorã in Figure 1a) by the following formula. [66] YðθÞ ¼…”
Section: Resultsmentioning
confidence: 99%
“…Besides hexagonal systems, the Dirac points can exist in 2D orthorhombic and tetragonal systems, including α-graphdiyne, [40] S-graphene, [41] palgraphyne, [10] and HOT graphene. [42] Further, azugraphene, [43] StoneÀWales graphene, [44] borophosphene, [45] cp-graphyne, [19] and circumcoro-graphyne [46] also exhibit linear band dispersion and associated Dirac points. However, most of the synthesized 2D carbon materials are protected by hexagonal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Table 6 contains the cohesive energies and structural data of the groups of related monolayers BX, 131,[136][137][138][139][140][141][142] AlX, 131,142,143 GaX, 131,134,142,144,145 InX, 131,134,142,146,147 and TlX 131,148 with X = N, P, As, Sb, and Bi. As revealed in Fig.…”
Section: Group Iii-v Monolayersmentioning
confidence: 99%
“…Due to the periodic affinity sites and excellent surface electrochemical properties, boron-phosphide monolayers can be expected to use as anode materials for lithium-ion batteries and anchoring materials for lithium-ion batteries [14,15]. In addition, its isomer with orthorhombic symmetry was proposed using the genetic algorithm methods [16], which holds great promise in alkali metal ion battery [17,18]. Although the boron-phosphide monolayer has not been synthesized, many studies have shown its great potential in nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%